The Whitefly, Bemisia tabaci (Homoptera: Aleyrodidae) Interaction with Geminivirus-Infected Host Plants Bemisia tabaci, Host Plants and Geminiviruses - Thompson, Winston M.O (Springer Netherlands : Imprint: Springer, 2011)
This Book will be of tremendous value since it introduces the different Bemisia tabaci -Geminivirus pathosystems along with the most recent findings and research endeavors. The various systems, each with its own challenge and complexity will unequivocally contribute to existing knowledge. With evolving geminiviruses and the appearance of new B. tabaci genetic groups, new interaction events and disease epidemics can be anticipated. To this end, chapters are included to deal with geminiviruses of economic importance, and the important molecular techniques used in B. tabaci identification and research. This Book will be an excellent reference source, comprising related chapters devoted to an improved understanding of the intricacies underlying geminivirus disease epidemics in various parts of the world. Since the ultimate goal is to advance such understanding into sustainable management practices against B. tabaci and the geminiviruses they transmit, concluding chapters deal with management, and possible applications of Remote Sensing and Geographic Information Systems (GIS) technology.        This book will be unique in that it emphasizes the various interaction systems involving B. tabaci and begomovirus-infected host plants as the proposed title suggest "The Whitefly, Bemisia tabaci (Gennadius) (Homoptera: Aleyrodidae) interaction with geminivirus-infected host plants" and it is anticipated to command a wide readership among academics, students and, professionals in the agricultural and life sciences.